Acute necrotizing encephalopathy with organic psychosis: a pediatric case report - Orgun, Leman Tekin; Arhan, Ebru; Aydın, Kürşad; Torun, Yasemin Taş; Güney, Esra; Serdaroğlu, Ayşe (The Turkish Journal of Pediatrics, 2020)
Background. Enteroviruses-associated acute necrotizing encephalopathy (ANE) of childhood is rarely reported in the literature. Clinico-radiological features of ANE are well-recognized and bilateral thalamic nuclei are frequently affected by ANE. Neuropsychiatric symptoms are rarely seen. Thalamic damage can cause psychosis. Case. Herein, we present a pediatric case of enterovirus-associated ANE presenting with psychosis related to thalamus damage in whom a favorable response to treatment was achieved. Conclusion. Thalamic damage occurs during the Enteroviruses-associated acute necrotizing encephalopathy and it can be related psychiatric sympthoms. Clinicians should be aware of uncommon presentations of ANE, and patients with thalamic damage should be followed for neuropsychiatric manifestations. Early recognition and appropriate treatment of ANE is important to obtain favorable outcomes.
Keywords: childhood; encephalopathy; enterovirus; psychosis; thalamus damage